A Handbook of Economic Anthropology, Second Edition - Carrier, James G. (Edward Elgar Publishing, 2012)
Acclaim for the first edition: 'The volume is a remarkable contribution to economic anthropology and will no doubt be a fundamental tool for students, scholars, and experts in the sub-discipline.' _ Mao Mollona, Journal of the Royal Anthropologica
Keywords: business & economics; cultural anthropology; cultural policy; economic anthropology; macroeconomics; political science; popular culture; public policy; social science

Textos escogidos. Karl Polanyi - Coraggio, J.L. (Buenos Aires : Consejo Latinoamericano de Ciencias Sociales (CLACSO) ; Los Polvorines, Provincia de Buenos Aires : Universidad Nacional de General Sarmiento, 2012)
Contents of book: Primera parte: Karl Polanyi y su obra: Actualidad de Karl Polanyi / Jean-Louis Laville. Karl Polanyi : su vida y época / Marguerite Mendell y Kari Polanyi Levitt. Karl Polanyi y la otra economía en América Latina / José Luis Coraggio -- Segunda parte: Los ensayos de Karl Polanyi: El lugar de las economías en las sociedades (1957) ; La economía como proceso instituido (1957) ; Aristóteles descubre la economía (1957) ; Feudalismo primitivo y feudalismo de la decadencia (1950) ; Marxismo e historia económica (comentario a Maurice Dobb) (1947) ; Comerciantes y comercio (1951) ; Semántica de los usos de la moneda (1957) ; Economía y democracia (1932) ; La esencia del fascismo (1935). El fascismo y la terminología marxista (1934) ; El marxismo redefinido (1934) ; Marx sobre el corporativismo (1934-1937) ; El cristianismo y la vida económica (1934-1937) ; Comunidad y sociedad : la crítica cristiana a nuestro orden social (1937) ; ¿Capitalismo universal o planificación regional? (1945) ; El significado de la democracia parlamentaria (1944-1945) ; Nuestra obsoleta mentalidad de mercado (1947) ; Sobre la creencia en el determinismo económico (1947) ; Jean-Jacques Rousseau o ¿Es posible una sociedad libre? ; La libertad y la tecnología (1955) ; La máquina y el descubrimiento de la sociedad (1957) ; La libertad en una sociedad compleja (1957) ; La sociedad opulenta según Aristóteles (1959).
Keywords: antropología económica; economic anthropology; economic history; economics; economía; historia económica